1996
DOI: 10.1159/000218001
|View full text |Cite
|
Sign up to set email alerts
|

Do Neuron-Specific Enolase Levels Discriminate between Small-Cell Lung Cancer and Mediastinal Tumors?

Abstract: The capacity of pretherapeutically assessed neuron-specific enolase (NSE) to differentiate between small cell lung cancer (SCLC) and mediastinal tumors was investigated retrospectively in a series of 320 patients. NSE was found to be increased in 95/130 (73.1%) patients with SCLC, in 4/62 (6.5%) patients with Hodgkin’s disease, in 10/58 (17.2%) patients with non-Hodgkin’s lymphoma, in 5/16 (31.3%) patients with teratoma, and in 6/54 (11.1 %) patients with thymoma. The cut-off value, defined as the 95% percenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…Of the 50 lung cancer patients with NSE levels above 100 ng/ml, 44 suffered from SCLC (23.4% of all SCLC patients) and six from NSCLC (1.6% of all NSCLC patients). These figures are in good agreement with the EGTM recommendations (40). However, these findings also show that the definite diagnosis in an individual patient cannot be made on the basis of NSE level.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Of the 50 lung cancer patients with NSE levels above 100 ng/ml, 44 suffered from SCLC (23.4% of all SCLC patients) and six from NSCLC (1.6% of all NSCLC patients). These figures are in good agreement with the EGTM recommendations (40). However, these findings also show that the definite diagnosis in an individual patient cannot be made on the basis of NSE level.…”
Section: Discussionsupporting
confidence: 88%
“…Also, NSE is not able to differentiate unequivocally between SCLC and mediastinal tumors such as thymoma, teratoma and Hodgkin's and non-Hodgkin's lymphomas. Elevated NSE was also reported in 13.2% of the latter tumors (40). This is of particular importance because both malignancies express similar roentgenographic features, presenting with a hilar mass and mediastinal widening.…”
Section: Discussionmentioning
confidence: 79%
“…6) As for malignant lymphomas, elevation of serum NSE levels was reported in 17 to 21% of NHL and 6.5 to 23% of Hodgkin's disease. 5,6) Values of NSE in the serum were reported to be 3.1±0.9 ng/ml in healthy individuals 13) and to range from 5 to 22 (median 10) ng/ml in NHL. 6) Whether serum NSE levels correlated with stage or histology of NHL was not mentioned in the previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…Though the serum concentration of NSE is seldom assayed in patients with malignant lymphoma, there are reports of the elevation of serum concentration of NSE in 17 to 21% of cases with non-Hodgkin's lymphoma (NHL). 5,6) Pyothorax-associated lymphoma (PAL) is a B-cell lymphoma developing in the pleural cavity of patients with over 20 years' history of chronic pyothorax resulting from artificial pneumothorax for the treatment of pulmonary tuberculosis or tuberculous pleuritis. 7,8) PAL is one of the Epstein-Barr virus (EBV)-associated lymphomas, and expresses latent genes of EBV including latent membrane proteins and EB nuclear antigens.…”
mentioning
confidence: 99%
“…However, not every case of foetal neuroblastoma shows increased NSE levels (12). Von Schweinitz et al (13) reported slightly increased NSE values in 3 of 7 cases of hepatoblastoma and Ebert et al (14) in 5 of 16 patients with teratoma. On the other hand haemolysis in blood samples leads to higher NSE values and should be excluded by inspection of serum after centrifugation.…”
Section: Discussionmentioning
confidence: 99%